Opposing functions of the Hda1 complex and histone H2B mono-ubiquitylation in regulating cryptic transcription in Saccharomyces cerevisiae. Issue 11 (31st August 2021) - Shirra, Margaret K; Kocik, Rachel A; Ellison, Mitchell A; Arndt, Karen M
Abstract: Maintenance of chromatin structure under the disruptive force of transcription requires cooperation among numerous regulatory factors. Histone post-translational modifications can regulate nucleosome stability and influence the disassembly and reassembly of nucleosomes during transcription elongation. The Paf1 transcription elongation complex, Paf1C, is required for several transcription-coupled histone modifications, including the mono-ubiquitylation of H2B. In Saccharomyces cerevisiae, amino acid substitutions in the Rtf1 subunit of Paf1C greatly diminish H2B ubiquitylation and cause transcription to initiate at a cryptic promoter within the coding region of the FLO8 gene, an indicator of chromatin disruption. In a genetic screen to identify factors that functionally interact with Paf1C, we identified mutations in HDA3, a gene encoding a subunit of the Hda1C histone deacetylase (HDAC), as suppressors of an rtf1 mutation. Absence of Hda1C also suppresses the cryptic initiation phenotype of other mutants defective in H2B ubiquitylation. The genetic interactions between Hda1C and the H2B ubiquitylation pathway appear specific: loss of Hda1C does not suppress the cryptic initiation phenotypes of other chromatin mutants and absence of other HDACs does not suppress the absence of H2B ubiquitylation. Providing further support for an appropriate balance of histone acetylation in regulating cryptic initiation, absence of the Sas3 histone acetyltransferase elevates cryptic initiation in rtf1 mutants. Our data suggest that the H2B ubiquitylation pathway and Hda1C coordinately regulate chromatin structure during transcription elongation and point to a potential role for a HDAC in supporting chromatin accessibility.